DNA Detection of Toxoplasma gondii with a Magnetic Molecular Beacon Probe via CdTe@Ni Quantum Dots as Energy Donor. (16th July 2013) - Xu, Shichao; Zhang, Chen; He, Lei; Wang, Tongyao; Ni, Liusong; Sun, Mengna; Miao, Heng; Zhang, Jimei; Dai, Zhao; Wang, Bing; Zheng, Guo
Abstract : A new method for detection of Toxoplasma gondii via DNA sensing technology was developed in this study. It was based on the mechanism of fluorescence resonance energy transfer (FRET) in which multifunctional and magnetic-fluorescent CdTe@Ni quantum dots (mQDs) were utilized as energy donor and a commercial BHQ2 as acceptor. The sensing probe was fabricated by labeling a stem-loop Toxoplasma gondii DNA oligonucleotide with CdTe@Ni mQDs at the 5′ end and BHQ2 at 3′ end, respectively. The surface assembly of CdTe on Ni core and the formation of CdTe@Ni were confirmed by XRD analysis. The sizes of CdTe, Ni nanoparticles, and CdTe@Ni were measured via TEM and XRD methods and estimated to be ~ 3 nm, ~ 15 nm, and ~ 20 nm, respectively. The sensing ability was investigated by the fluorescence spectrum (FS). An obvious fluorescence recovery was observed when the complete complimentary target Toxoplasma gondii DNA was introduced, which did not happen in the case of the target DNA with one-base pair mismatch. Our research indicates that the current sensing probe is sensitive and specific in detection of Toxoplasma gondii DNA and has great potential in Toxoplasmosis diagnosis.